Literature Review : Peningkatan Literasi Lingkungan Siswa di Sekolah - Karmana, I Wayan (Biocaster : Jurnal Kajian Biologi, 2023)
Nowadays, environmental problems have become a global issue that is widely discussed. Environmental problems that occur are caused by climate change, the extinction of natural resources, to environmental damage caused by human activities. One of the causes of low public awareness of the environment is the low ability of community environmental literacy. One of the efforts to improve environmental literacy is through formal education by implementing learning activities that are able to improve students' environmental literacy skills. Writing this article aims to find out ways or efforts to increase students' environmental literacy in schools with the literature review method, namely, a literature search to collect data from various sources such as journals, books, the internet, and other libraries. Based on the journal reviews that have been carried out, there are several efforts that can be made to optimize or improve environmental literacy in schools, including by structuring the curriculum, conducting learning that provides direct experience supported by active learning using a variety of varied methods and its implementation can be carried out inside or outside outside the classroom, using problem-solving-based learning models, implementing adiwiyata programs, and using interesting learning media.